PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA VIDEO UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMATIK DI KELAS IV SD - Nayoga Yuswantoro; Adi, Adi Winanto (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
Abstract: Education is an integral part of development. Learning can also be interpreted as the result of an experience in the form of interaction with learning resources such as environment, books, or people. Learning outcomes are not a mastery of training results, but the creation of aspects of knowledge, skills, and attitudes of students. During the learning process, it appears that the teacher is less maximal in implementing the 2013 curriculum with innovative creative learning models and the teacher does not integrate various lesson content into predetermined themes. This has an impact on student learning outcomes when learning has been carried out face to face. The research conducted aims to improve student learning outcomes when using the Problem Based Learning model on thematic learning for grades IV Elementary School. This research is a classroom action research with two cycles. The population in this study was 21 and the samples used were saturated samples. The instruments in this study were observations and tests of student learning outcomes. Data collection techniques in this research for observations were taken by supervisors, they are elementary school teachers and learning outcomes tests for students in thematic learning. The data analysis technique in this research is descriptive analysis and N-gain test. The results showed that there was an increase in average learning outcomes and the proportion of mastery. In the N-gain test, the increase was in medium category. This is because the use of PBL in thematic learning raises daily life material so that it is easier for students to carry out the projects they are working on to improve their learning outcomes. Keywords: Problem Based Learning, Video Media, Learning Outcomes